Pengaruh Konsentrasi Monomer Terhadap Pembentukan Poli Kuersetin Sebagai Zat Warna pada Dye Sensitized Solar Cell - Putri, Yollanda Prissila; Hardeli, Hardeli (Departemen Kimia FMIPA UNP, 2023)
Dye-Sensitized Solar Cell (DSSC) is a type of dye-based third-generation solar cell that functions as a photon absorber. Modifications were made to the quercetin dye to increase the double bonds, and the semiconductor used was done with TiO2 – ZnO doping. Doping can reduce the energy gap, thereby increasing the conductivity of TiO2. The TiO2 – ZnO layer was made by the doctor blade method on ITO glass and the dye was immersed in poly quercetin. The DSSC circuit is arranged to form a sandwich facing each other, between the working electrode and the counter electrode. DSSC efficiency can be tested from the results of resistance and voltage measurements on UV light with a power of 24 watt/m2 using a digital multimeter. The highest efficiency was produced at a monomer concentration of 2.5 grams of 9.4% from a long polymer chain.